All Days 2002
DOI: 10.2118/75241-ms
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Visualization with High Resolution Optical-Fiber Scope at Steam Chamber Interface on Initial Stage of SAGD Process

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractExperiments and numerical simulations on initial stages of the steam-assisted gravity drainage (SAGD) process were carried out. Experimental studies used two-dimensional scaled reservoir models to investigate fluids flow characteristics in the steam chamber and production fluids. The rise and growth of the initial steam chamber were observed and visualization of micro-phenomena at inclined interface on the side of the steam chamber with a high-resolution opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 4 publications
1
32
1
Order By: Relevance
“…Very fine water droplets produced at the chamber interface due to the condensation would move likely into the oil face (which has already been mobilized as a result of direct steam heating) immediately after generation. This microscopic invasion of very fine water droplets (in the order of 0.005 to 0.01mm in diameter) into the bitumen-filled region would likely create water-in-oil emulsions which should be drained under the resultant force of gravity-capillarity interaction [28]. This emulsification hypothesis on a plane interface is illustrated schematically in Figure 4a.…”
Section: Emulsification Phenomenonmentioning
confidence: 99%
See 2 more Smart Citations
“…Very fine water droplets produced at the chamber interface due to the condensation would move likely into the oil face (which has already been mobilized as a result of direct steam heating) immediately after generation. This microscopic invasion of very fine water droplets (in the order of 0.005 to 0.01mm in diameter) into the bitumen-filled region would likely create water-in-oil emulsions which should be drained under the resultant force of gravity-capillarity interaction [28]. This emulsification hypothesis on a plane interface is illustrated schematically in Figure 4a.…”
Section: Emulsification Phenomenonmentioning
confidence: 99%
“…The topic of "emulsification phenomenon" during the typical SAGD process was covered in the literature based on the experiments conducted using scaled physical models as well as field-scale data [24,[26][27][28][29][30][31]. According to the field-scale trials of the SAGD process, the produced liquid is in the emulsion state composed of mobilized oil and water (either stable or unstable depending on the physicochemical characteristics of the interacting liquids as well as process operating conditions).…”
Section: Emulsification Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…An excellent review of current status and future issues on SAGD was presented by Al-Bahlani and Babadagli [1] in terms of experimental and numerical studies. As mentioned in their review, Sasaki et al [3] suggested the in-situ emulsification mechanism in the SAGD process as shown in Fig. 1.…”
Section: Introduction mentioning
confidence: 97%
“…In addition, the surface action of oil D DAVID PUBLISHING Fig. 1 Mechanism of SAGD process and in-situ emulsification modified from Sasaki et al [3].…”
Section: Introduction mentioning
confidence: 99%